2022
DOI: 10.1158/1538-7445.am2022-2104
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2104: NK cell immunosurveillance of tumors is regulated by NFAT1 and NFAT2

Abstract: NK cells are lymphoid components of innate immunity and play an important role in tumor immunosurveillance. One of the major transcriptional regulators in lymphoid cells is NFAT (Nuclear Factor of Activated T cells), controlling lymphocyte development and activity. However, while the role of NFAT signaling is well defined in T cells, the cytotoxic lymphocytes of adaptive immunity, surprisingly little is known regarding the relevance of this transcription factor family in NK cells as effector cells of innate im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Exposure to sµG also led to a signi cant up-regulation of the following transcripts (Fig. 7): 1) CD3D (p = 1.14e − 3 ), which is consistent with the recently described NK2.4 subset of memory-like NK cells that accumulates with aging and exhibits low expression of the TCR complex 48 ; 2) CD5 (p = 6.6e − 3 ), a cell surface protein that has an inhibitory function in antigen receptor signaling and is not normally expressed on NK cells and would be expected to impair NK functionality [49][50][51] ; 3) decay-accelerating factor/CD55 (p = 8.53e − 3 ), a molecule whose expression has been shown to inhibit human NK cell cytotoxicity against hematological cancers 52 ; 4) CD84 (p = 0.01), engagement of which signi cantly dampens NK cell cytotoxicity 53 ; 5) CD200 (p = 0.02), the shedding of which in the tumor microenvironment leads to NK cell dysfunction and apoptosis 54 ; 6) CD47 (p = 0.05), a nding of particular relevance to the anti-tumor function of NK cells, since prior studies have shown that CD47 may play an inhibitory role in NK cell-mediated cytotoxicity against cancer cells 55 ; 7) LAIR1 (p = 0.01), a potent inhibitor of NK cytotoxicity 56 ; 8) NFATC1 (p = 0.02), a negative regulator of NK cell tumor immunosurveillance 57 ; and 9) CD34 (p = 7.6e − 3 ), an antigen only present on the earliest precursors of the NK lineage 58 , suggesting that microgravity may provoke a regression of NK cells to an immature, undifferentiated stem-like state, as has been reported with other cell types grown in microgravity 59,60 .…”
Section: Rna-seq To Delineate Mechanism(s) Whereby Sµg Reduces Nk Cyt...mentioning
confidence: 99%
“…Exposure to sµG also led to a signi cant up-regulation of the following transcripts (Fig. 7): 1) CD3D (p = 1.14e − 3 ), which is consistent with the recently described NK2.4 subset of memory-like NK cells that accumulates with aging and exhibits low expression of the TCR complex 48 ; 2) CD5 (p = 6.6e − 3 ), a cell surface protein that has an inhibitory function in antigen receptor signaling and is not normally expressed on NK cells and would be expected to impair NK functionality [49][50][51] ; 3) decay-accelerating factor/CD55 (p = 8.53e − 3 ), a molecule whose expression has been shown to inhibit human NK cell cytotoxicity against hematological cancers 52 ; 4) CD84 (p = 0.01), engagement of which signi cantly dampens NK cell cytotoxicity 53 ; 5) CD200 (p = 0.02), the shedding of which in the tumor microenvironment leads to NK cell dysfunction and apoptosis 54 ; 6) CD47 (p = 0.05), a nding of particular relevance to the anti-tumor function of NK cells, since prior studies have shown that CD47 may play an inhibitory role in NK cell-mediated cytotoxicity against cancer cells 55 ; 7) LAIR1 (p = 0.01), a potent inhibitor of NK cytotoxicity 56 ; 8) NFATC1 (p = 0.02), a negative regulator of NK cell tumor immunosurveillance 57 ; and 9) CD34 (p = 7.6e − 3 ), an antigen only present on the earliest precursors of the NK lineage 58 , suggesting that microgravity may provoke a regression of NK cells to an immature, undifferentiated stem-like state, as has been reported with other cell types grown in microgravity 59,60 .…”
Section: Rna-seq To Delineate Mechanism(s) Whereby Sµg Reduces Nk Cyt...mentioning
confidence: 99%